A comparison on microstructure features of 24CrNiMo low alloy steel prepared by selective laser melting and laser melting deposition. (September 2021) - Cui, X.; Zhang, S.; Zhang, C.H.; Chen, J.; Zhang, J.B.; Dong, S.Y.
Abstract: In this study, microstructural features of 24CrNiMo low alloy steel fabricated by selective laser melting (SLM) and laser melting deposition (LMD) were characterized and compared using advanced electron microscopy and electron backscatter diffraction techniques. The results showed that the microstructures with different microstructure types, crystallographic orientations, grain boundaries, grain sizes, dislocations distributions and slip capabilities were observed due to rather different thermal histories between SLM and LMD processes. Such differences in the microstructure can definitely lead to different mechanical properties. This work can provide a reference for the process choice based on practical industrial applications. Highlights: 24CrNiMo steel was prepared successfully by two additive manufacturing techniques. Direct comparison of 24CrNiMo steel prepared via two methods was carried out. Various thermal histories caused different microstructural features in two cases.